ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN (Studi Perusahaan Manufaktur PMA dan PMDN yang terdaftar di BEI) - Cicha Putri Apriliyani; Rony Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe profitability of manufacturing companies in Indonesia is influenced by financial factors that can be measured in the company's financial ratios in order to analyze the impact of a country.The population of this study is PMA and PMDN manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2019, Purposive sampling method used as a sampling method of 28 companies selected as research samples.The analytical method used is multiple regression using dummy variables. The results of the study used t-test, namely cash turnover and company status, have a positive effect on investment returns, while working capital turnover has a significant negative impact on investment returns, inventory turnover is not a lot of impact on investment returns.Keywords: Return on investment (ROI), working capital turnover, cash turnover, inventory turnover, company status.